Prediksi Penjualan Mi Menggunakan Metode Extreme Learning Machine (ELM) di Kober Mie Setan Cabang Soekarno Hatta - Ayustina Giusti; Agus Wahyu Widodo; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Kober Mie Satan Soekarno Hatta branch is a company engaged in the field of food. The number of consumer demand of restaurant Kober Mie Setan Soekarno Hatta branch that is erratic every time affect the remaining raw materials. Raw materials that are stored for too long are not good for consumption. When demand is low and the raw materials provided are high, then the rest of the raw materials from the day's sales will be discarded. In order for raw materials are not wasted, then the sales prediction required by Kober Mie Setan Sukarno Hatta branch. With these sales predictions the restaurant can prioritize the expenditure of certain menu ingredients that have a high interest so that the remaining raw materials can be reduced. This research applies method of artificial neural network (JST) that is Extreme Learning Machine (ELM) to predict the sales of noodles in Kober Mie Setan restaurant of Soekarno Hatta branch. The prediction process of noodles sales in Kober Mie Setan is normalization of data, training process, testing process, data denormalization, and error value calculation using Mean Square Error (MSE). ELM method has advantages in learning speed and small error rate. Based on the tests conducted to determine the differences in the use of data features in this study resulted in the smallest error rate of 0.0171 using the features of historical data and features of residual sales data.